2018
DOI: 10.1101/353441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subjugation of TGFβ Signaling by Human Papilloma Virus in Head and Neck Squamous Cell Carcinoma Shifts DNA Repair from Homologous Recombination to Alternative End-Joining

Abstract: Purpose: Following cytotoxic therapy, 70% of patients with human papillomavirus (HPV) positive oropharyngeal head and neck squamous cell carcinoma (HNSCC) are alive at 5 years compared to 30% of those with similar HPV-negative cancer, which is thought to be due to dysregulation of DNA repair. Loss of transforming growth factor β (TGFβ) signaling is a poorly studied consequence of HPV that could contribute to this phenotype.Experimental Design: Human HNSCC cell lines (n=9), patient-derived xenografts (n=9), tis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 57 publications
3
29
0
Order By: Relevance
“…Previous studies reported that low HRR capacity of the HPV‐positive HNSCC could explain the sensitivity to PARP inhibition alone or in combination with RT . Others have hypothesized that the reliance of HPV‐positive HNSCC on alternative EJ could provide a mechanistic explanation for the sensitivity to PARP inhibitors . In addition, dependency of PARP inhibition alone or in combination with RT is also reported to be independent of HPV‐status, but related to defects in HRR, impaired or DSB repair or increased ROS production …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that low HRR capacity of the HPV‐positive HNSCC could explain the sensitivity to PARP inhibition alone or in combination with RT . Others have hypothesized that the reliance of HPV‐positive HNSCC on alternative EJ could provide a mechanistic explanation for the sensitivity to PARP inhibitors . In addition, dependency of PARP inhibition alone or in combination with RT is also reported to be independent of HPV‐status, but related to defects in HRR, impaired or DSB repair or increased ROS production …”
Section: Discussionmentioning
confidence: 99%
“…29,30 Others have hypothesized that the reliance of HPV-positive HNSCC on alternative EJ could provide a mechanistic explanation for the sensitivity to PARP inhibitors. 15 In addition, dependency of PARP inhibition alone or in combination with RT is also reported to be independent of HPV-status, 31 but related to defects in HRR, 32 impaired or DSB repair 33 or increased ROS production. 34 Here, we show that the enhanced sensitivity to PARP inhibition could be linked to higher activity of the BER pathway in HPV-positive HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HPV is an important risk factor for HNSCC, and is associated with tumor biology and clinical characteristics including response to radiation (3,6,20). Recently, the involvement of HPV in the radiosensitivity of cancers has been established through altered tumor immune microenvironment.…”
Section: Figurementioning
confidence: 99%